PEMECAHAN MASALAH SISWA PADA MATERI TEOREMA PYTHAGORAS BERDASARKAN KEMAMPUAN MATEMATIKA - Pathuddin Pathuddin; Alfisyahra Alfisyahra; Desti Desti; Evie Awuy (HISTOGRAM: Jurnal Pendidikan Matematika, 2023)
Student problem solving needs to be analyzed so that the teacher can know how students solve problems on math problems. This study aims to obtain a description of the problem-solving analysis of grade VIII students of SMP Negeri 1 Tomini who have high, medium, and low mathematical abilities in solving pythagorean theorem problems. This type of research is qualitative research. The subjects of this study were 3 students taken from 24 class VIII students of SMP Negeri 1 Tomini in the even semester of 2021/2022. The results of this study show that subjects with high mathematical ability can solve well the four steps or indicators of problem solving namely (Understanding the problem, drawing up a plan, implementing a plan and re-examining). A moderately mathematics capable subject can complete 2 steps or indicators of problem solving, i.e. (Understanding the problem, and checking back).Â  On the second and third indicators the subject is not able to solve the problem. Subjects with low mathematical ability can only complete the first stage which is to understand the problem.